Long-term Effect of Chemo-Intensity-Modulated Radiation Therapy (chemo-IMRT) on Dentofacial Development in Head and Neck Rhabdomyosarcoma Patients - Owosho, Adepitan A. (Pediatr Hematol Oncol, 2016)
Dentofacial developmental abnormalities have been reported in head and neck rhabdomyosarcoma (HNRMS) patients treated with conventional radiotherapy technique and chemotherapy. This current study investigates dentofacial long-term effects among HNRMS survivors managed with intensity-modulated radiotherapy (IMRT) and chemotherapy. In general, IMRT is a more effective 3D-conformal radiotherapy technique, which delivers high doses of radiation to the tumor target while minimizing doses received by the surrounding normal tissues. The medical records and radiographs were reviewed to identify the following: 1. Facial asymmetry and jaw hypoplasia. 2. Effects on the dental tissue causing tooth agenesis/hypodontia, root agenesis/stunting/malformation, and/or enamel hypoplasia. 3. Trismus, hyposalivation/xerostomia. Thirteen patients reviewed were evaluated at the dental service. Seven patients presented with facial asymmetry and jaw hypoplasia, 9 patients presented with effects on the dental tissue [root agenesis/stunting/malformation (9), tooth agenesis/hypodontia (7) and enamel hypoplasia (3)] and 7 patients developed trismus and /or xerostomia. All patients with facial asymmetry and jaw hypoplasia also developed dental abnormalities. Patients with dentofacial developmental abnormalities were ≤ 7 years of age at treatment. Our study shows that dentofacial developmental abnormalities are still a burden in the era of IMRT and as prognosis of childhood malignancy improves and more patients become long-term survivors, these late dentofacial sequelae among childhood cancer survivors will be common. To minimize these complications, dental oncologists should be integrated into the care of children with head and neck cancers.